2014
DOI: 10.2478/raon-2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

Circulating serum sVCAM-1 concentration in advanced ovarian cancer patients: correlation with concentration in ascites

Abstract: BackgroundVascular cell adhesion molecule-1 (VCAM-1) is associated with ovarian cancer progression but the origin of its soluble form (sVCAM-1) in serum is not well investigated. The purpose of this study was to elucidate whether the concentration of sVCAM-1 in serum correlates with the concentration in ascites, that represents local tumour environment, and with systemic inflammation, various clinicopathological characteristics, and patient outcome.Patients and methods.Thirty-six patients with advanced ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…One small cohort study of 36 ovarian cancer patients identified significantly elevated sVCAM-1 in 5 patients who died within 11 months of follow-up compared to the 31 who were alive (27). Another report found no association between sVCAM-1 and outcome among ovarian cancer patients (n=50) but was able to identify patients with metastatic disease (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One small cohort study of 36 ovarian cancer patients identified significantly elevated sVCAM-1 in 5 patients who died within 11 months of follow-up compared to the 31 who were alive (27). Another report found no association between sVCAM-1 and outcome among ovarian cancer patients (n=50) but was able to identify patients with metastatic disease (28).…”
Section: Discussionmentioning
confidence: 99%
“…patients who died within 11 months of follow-up compared with the 31 who were alive. 27 Another study found no association between sVCAM-1 and outcome among ovarian cancer patients (n 5 50) but identified patients with metastatic disease. 28 The primary objective of our study was to link sVCAM-1 to mesothelium VCAM-1 expression with the expectation that it could serve as a surrogate prognosticator.…”
Section: Vcam-1 and Ovarian Cancer Outcome/scalici Et Almentioning
confidence: 96%
“…The data in this study are derived from a small pilot study, but is representative of our institutional clinical practice in regard to OC histology and stage distribution as well as published pilot studies examining IL-1β in urine, serum, and plasma [17,56,[58][59][60][61] and other clinically relevant pilot studies [62][63][64][65][66]. A normal baseline value for urinary IL-1β in women has not yet been established in the literature [67].…”
Section: Discussionmentioning
confidence: 99%
“…One such protein has been Soluble Vascular Cell Adhesion Molecule-1 (sVCAM-1). 3 Its elevated concentration is shown to be associated with tumor presence. 4 Expressed on activated endothelial and mesothelial cells VCAM-1 has been identified as an important mediator for adhesion of ovarian cancer cells to and invasion through the mesothelium.…”
Section: Introductionmentioning
confidence: 99%